2010
DOI: 10.2355/isijinternational.50.1606
|View full text |Cite
|
Sign up to set email alerts
|

The Composition and Morphology Evolution of Oxide Inclusions in Ti-bearing Ultra Low-carbon Steel Melt Refined in the RH Process

Abstract: Before deoxidation, the main inclusions were Fe-Mn-O inclusions in Ti-bearing ultra low-carbon steel melt. After 3 min Al addition, the inclusions changed to be granular and spherical Al 2 O 3 . Al 2 O 3 cluster, composed of granular and spherical particles with diameter 1-2 mm, formed in 7 to 10 min after Al addition into the melt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 18 publications
1
34
2
Order By: Relevance
“…The number of particles per area is then calculated by Equation V=ΔOFeTitrue(Otrue)Al2normalO3ρFeρAl2normalO3 NV=6Vπd¯3 Na=NVπd¯Z …”
Section: Resultsmentioning
confidence: 99%
“…The number of particles per area is then calculated by Equation V=ΔOFeTitrue(Otrue)Al2normalO3ρFeρAl2normalO3 NV=6Vπd¯3 Na=NVπd¯Z …”
Section: Resultsmentioning
confidence: 99%
“…x/3 Al2O3 (s) + Ti = TiOx (s) + 2x/3 Al .......... (7) Al2O3 (s) + m Ti = Al2-nTimO3(s) + nAl.......... (8) It was also assumed that the elemental species like Al and Ti were in the dissolved state because of the partial melting inside the FeTi35 as can be seen from Fig. 12(c).…”
Section: Inclusion Evolutionmentioning
confidence: 99%
“…On an industrial scale also, clusters of Al-Ti-O inclusions after the addition of FeTi to Al-killed steel at the end of RH treatment have been reported. 8) The addition sequence of Al and Ti has been studied in detail 9) to analyze its influence on inclusion behavior. It was observed that irrespective of the addition time of Al or Ti, the final chemistry of the inclusions was alumina.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, the interaction between existing NMI in liquid steel and the various installations is in the center of attention for secondary refining process. Recently, details of the inclusion formation of Ti-alloyed Al-killed steel grades [1][2][3][4][5] and its physical and chemical development during reoxidation are receiving considerable attention. From these studies, it is being recognized that inclusions in the Al-Ti-Fe-O system may react sensitively on the details of the secondary steelmaking treatment, such as the oxygen balance achieved.…”
Section: Introductionmentioning
confidence: 99%